2010
DOI: 10.1111/j.1464-5491.2009.02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different techniques for subcutaneous glucose monitoring in Type 1 diabetic patients during ‘real‐life’ glucose excursions

Abstract: The three investigated technologies had comparable performance. Whereas GRT underestimated actual blood glucose, GDS and MD overestimated blood glucose. Considerable deviations during daily life meal glucose excursions from reference glucose were observed for all three investigated technologies. Present technologies may require further improvement until individual data can lead to direct and automated generation of therapeutic advice in diabetes management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…3) were similar to or better than those recently observed with commercial continuous glucose sensing devices that use the ISF of insulin-unexposed adipose tissue for the measurement of glucose. 6,[20][21][22][23][24][25][26] For example, recent studies assessing the accuracy of these continuous glucose sensing devices have observed median ARD values (range, 7.7-19.7%) that are similar to 6,20,22 or higher than 21,[23][24][25][26] the median ARD value derived in the present study (8.0%). Furthermore, in a recent study performed in subjects with diabetes, 14 we have assessed the agreement between the plasma glucose concentrations and the ISF glucose levels observed at the insulin delivery site during uninterrupted CSII.…”
Section: Fig 2 (Left Page and Above)supporting
confidence: 49%
See 1 more Smart Citation
“…3) were similar to or better than those recently observed with commercial continuous glucose sensing devices that use the ISF of insulin-unexposed adipose tissue for the measurement of glucose. 6,[20][21][22][23][24][25][26] For example, recent studies assessing the accuracy of these continuous glucose sensing devices have observed median ARD values (range, 7.7-19.7%) that are similar to 6,20,22 or higher than 21,[23][24][25][26] the median ARD value derived in the present study (8.0%). Furthermore, in a recent study performed in subjects with diabetes, 14 we have assessed the agreement between the plasma glucose concentrations and the ISF glucose levels observed at the insulin delivery site during uninterrupted CSII.…”
Section: Fig 2 (Left Page and Above)supporting
confidence: 49%
“…Overall, these results suggest that estimation of plasma glucose concentrations from the glucose levels observed at the insulin delivery site during both CSII and shortterm interruptions of CSII is feasible and its quality is similar to or better than that of estimating plasma glucose concentrations from glucose levels measured in insulin-unexposed subcutaneous tissue using the latest commercial continuous glucose sensing devices. 6,[20][21][22][23][24][25][26] Therefore, glucose monitoring and insulin delivery could be carried out both simultaneously or sequentially at the same adipose tissue site using a single tissue catheter (single-port treatment approach), thereby leading to the possibility of simplifying and improving glucose management in diabetes.…”
Section: Fig 2 (Left Page and Above)mentioning
confidence: 99%
“…However, the differences between sites in mean agreement rate and mean ARD were not statistically significant, and mechanical disturbances were not assessed for possible effects on accuracy. Published accuracy studies [11][12][13] of Sof-Sensor attached to the Guardian REAL-Time System in adult subjects do not specify which site was used. We are, therefore, reporting the first published study to investigate whether the Sof-Sensor/NexSensor form factor is safe and accurate for use in the abdomen and buttocks sites.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative methods for glucose determination which decrease the workload for nursing staff could overcome these issues. Continuous subcutaneous glucose monitoring either by using commercially available continuous monitoring (CGM) systems 5 9 or by means of standard microdialysis 10 13 has been proven to accurately track changes in glucose concentration in both patients with type 1 and type 2 diabetes mellitus. Not only acute also long long-term clinical outcomes were found to be improved when using CGM systems.…”
Section: Introductionmentioning
confidence: 99%